2016
DOI: 10.1097/gox.0000000000000717
|View full text |Cite
|
Sign up to set email alerts
|

Malar Reconstruction Using Y-V Advancement Flaps after Tissue Expansion in Treacher Collins Syndrome

Abstract: Summary:The Treacher Collins syndrome is characterized by both soft and hard tissue deficiencies. To reconstruct malar hypoplasia with both soft and hard tissues, we designed a new method using cartilage grafts, Y-V advancement flaps, and Z plasty with tissue expansion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In addition to the dysplasia or defect of the orbitozygomatic bone, the soft tissue in the midface area also has hypoplasia to varying degrees in these patients, so simple reconstruction of the orbitozygomatic region sometimes does not bring significant results. Although some patients have orbitozygomatic dysplasia, the anterior one third of the zygomatic arch remains, the collapse of the orbitozygomatic region is not serious, so that the patient’s midface can be significantly improved by temporal expansion flap9 and autologous fat transplantation with reduced trauma. In the process of autologous fat transplantation, we found that the effect of it in children is better, which may be related to the improvement of local tissue blood supply and the development of surrounding tissues after fat survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the dysplasia or defect of the orbitozygomatic bone, the soft tissue in the midface area also has hypoplasia to varying degrees in these patients, so simple reconstruction of the orbitozygomatic region sometimes does not bring significant results. Although some patients have orbitozygomatic dysplasia, the anterior one third of the zygomatic arch remains, the collapse of the orbitozygomatic region is not serious, so that the patient’s midface can be significantly improved by temporal expansion flap9 and autologous fat transplantation with reduced trauma. In the process of autologous fat transplantation, we found that the effect of it in children is better, which may be related to the improvement of local tissue blood supply and the development of surrounding tissues after fat survival.…”
Section: Discussionmentioning
confidence: 99%
“…The children with Treacher-Collins syndrome have to be followed by a plastic surgeon because they may need a series of operations to correct birth defects. Receding chin and other changes in face structure can be corrected by plastic surgery [7][8][9].…”
mentioning
confidence: 99%